A Review on Reactor Design and Surface Modification of Atomic Layer Deposition for Functional Nanoparticles - Guanghui Yan; Gaoshan Huang; Jianjun Shi; Yi Ouyang; Xueqin Zuo; Zhihao Bao; Yongfeng Mei (Advanced Materials Interfaces)
Abstract Atomic layer deposition (ALD) has emerged as a promising method for surface modification of functional nanoparticles, enabling the versatile applications in energy, catalysis, and human health. The self‐limiting surface chemistry of ALD allows not only the coating of ultrathin and conformal films but also the decoration of nanoparticle surfaces with specific nanoclusters under appropriate processing conditions. In particle ALD, one of the major challenges lies in the strong cohesive force causing nanoparticle agglomerates or aggregates, which requires their homogeneous dispersion. This review provides an overview on the developments and advancements of particle ALD, covering both reactor designs and applications. The fundamentals of ALD are first reviewed, followed by the reactor designs including fluidized bed reactors, rotating bed reactors, and atmospheric‐pressure continuous spatial ALD reactors. Among them, the basics of particle fluidization are concisely outlined to establish a foundation for understanding fluidized bed reactors. The advantages and disadvantages of various reactor designs are compared and analyzed. Subsequently, the applications of ALD‐modified nanoparticles are reviewed, with a focus on energy, catalysis, biomedicine, and cosmetics. Finally, the progress and applications of ALD modification for functional nanoparticles are summarized, and the perspectives in the field are proposed.